2021
DOI: 10.1111/1751-7915.13734
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of hypocrellin B and curcumin on photodynamic inactivation of Staphylococcus aureus

Abstract: Photodynamic activity of HB against S. aureus was comprehensively profiled, and this effect can be strengthened by joint action with curcumin. HB/curcumin photo‐inactivated S. aureus through disrupting cell envelope integrity and inducing diverse set of oxidative stress, forming a synergistic aPDI method depending on the irradiated conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The combination of CUR and another natural PS, hypocrellin B, increased the photoinactivation of S. aureus compared with the photodynamic effect of each PS alone [32]. Bacterial cells showed alteration in their membrane integrity and the dual-PS-mediated aPDT also decontaminated apples with S. aureus [32]. The CUR-mediated aPDT was also effective in decontaminating food, reducing the number of S. aureus recovered from meat and fruit [33].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The combination of CUR and another natural PS, hypocrellin B, increased the photoinactivation of S. aureus compared with the photodynamic effect of each PS alone [32]. Bacterial cells showed alteration in their membrane integrity and the dual-PS-mediated aPDT also decontaminated apples with S. aureus [32]. The CUR-mediated aPDT was also effective in decontaminating food, reducing the number of S. aureus recovered from meat and fruit [33].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Bacterial growth can also be controlled using a new approach-photodynamic inactivation. Staphylococcus aureus growth was inhibited by the combination therapy of curcumin and hypocrellin B, where the photodynamic efficacy of hypocrellin B was potentiated by curcumin [75].…”
Section: Synergistic Effectsmentioning
confidence: 99%
“…To solve this issue, Tortik et al 90 reported that PDI by using curcumin (50-100 μM) and blue light (λ = 435 nm) of S. aureus and other food-borne microbes could be an effective way to make food stuffs microbe free. 91,92 This study may be further extended in which antibacterial activity of curcumin and chemical food preservatives (like benzoic acid, nitrites, sodium benzoate, sulfites, potassium sorbate, and sodium sorbate) may be tested together in future food processing research by mixing the natural and chemical preservatives in various proportions, thereby reducing the actual amount of chemical preservatives required in food processing industry. Ultrasound finds good application in the field of medicine and biology in recent years and has multiple advantages like low cost, safety and convenience of operation, and intense penetration in biological tissue.…”
Section: Curcumin and Its Various Nanoformulations-mediated Inhibitio...mentioning
confidence: 99%
“…In a nutshell and precisely, it can be inferred that nanocurcumin/nanocomposites and curcumin exhibit efficient anti‐ P. aeruginosa and antibiofilm activity by inhibiting the QS system, retarding release of components for biofilm formation, biofilm disruption, ROS‐mediated bacterial membrane, and ultrastructure damage 51–66,71–78 . Similarly, MRSA and MDR‐ S. aureus growth and biofilm can be effectively inhibited with nanocurcumin/nanocomposites and curcumin along with antibiotics, blue light‐mediated PDI, cell penetrating peptide, and so on, that generate singlet oxygen and other ROS, thereby causing bacterial membrane damage and cytoplasmic leakage 79–102 . Curcumin nanocomplex aerosols and crude curcumin (along with blue LED light‐activated EDTA) have the potential to inhibit B. cepacia growth by mechanism that includes bacterial DNA and protein damage and intracellular content leakage 103–109 .…”
Section: Mechanism Of Antibacterial Activity Of Curcumin Its Essentia...mentioning
confidence: 99%